In Vitro propagation of Pilosocereus robinii (Lemaire) Byles et Rowley, endemic and endangered cactus - Quiala, Elisa; Matos, Jesús; Montalvo, Grecia; de Feria, Manuel; Chávez, Maité; Capote, Alina; Pérez, Naivy; Barbón, Raúl; Kowalski, Britta (Journal of the Professional Association for Cactus Development, 2009)
In vitro propagation systems by areole activation were developed for Pilosocereus robinii (Lemaire) Byles et Rowley, an endemic cactus of Cuban island in extinction danger. Seeds from mature fruits were collected under field conditions and disinfected with two concentration of NaOCl (1.0 and 2.0%) and two time of disinfection (15 and 20 min). During germination a half- and full-strength MS basal medium were tested. The highest germination rate (92.8%) was reached when half MS basal medium were used. Shoot formation from areoles of in vitro-germinated plantlets was achieved in explants cultured in Murashige and Skoog (MS) basal medium supplemented with 30 g l-1 sucrose, 3.0 g l-1 Gelrite® and three concentration of 6-Bencilaminopurine (4.44, 6.66 and 13.32 ?M). Shoot production in this proliferation medium was evaluated during three culture cycles. Proportionately proliferation rate increase with 6-BAP concentration, on the contrary shoots length decreased. The highest proliferation rate (8.9 shoots per explant) was reached employment 13.32 ?M of 6-BAP. On average, rooting efficiency was 100% in MS basal medium free of growth regulators. The frequency of survival of the plants once transferred to substrate composed of cattle manure rotted for eight months was on average 91.6%. Finally, 500 individual plants of Pilosocereus robinii were transferred to nursery. We describe for the first time a system for the production of multiple shoots by areole activation, as well as their rooting, acclimatization and nursery establishment of endangered and endemic specie, that are difficult to propagate by conventional methods.